Self-reported life experiences of members of the LGBTQ+ community in Accra, Ghana - Donald Womonia Anuga; Merri Iddrisu; Kennedy Dodam Konlan (PLoS ONE, 2025)
Background Lesbian, Gay, Bisexual, Transgender, Queer/Questioning (LGBTQ+) community members encompass individuals whose sexual orientations and gender identities do not align with the heterosexual norms in society. Even though this population has gained increasing prominence worldwide, most societies particularly in sub-Saharan Africa (SSA) abhor these sexual orientations. We explored the self-reported life experiences of members of the LGBTQ+ community in Accra, Ghana. Methods In this qualitative enquiry, we recruited fifteen (15) members of the LGBTQ+ community in Accra via purposive snowballing sampling technique. We conducted in-depth interviews using a pre-tested interview guide and the interviews were audio taped and transcribed verbatim. Thematic analysis was conducted with the aid of NVivo 10.0. Results The participants recounted their experiences within their individual families, within the LGBTQ+ community, and their experiences with the public in Ghana and as well as within their extended families. The participants claimed that the general society (public) in Ghana stigmatizes against members of the LGBTQ+ community with most families rejecting members who claim to be LGBTQ+ persons. The participants however claimed that the LGBTQ+ community served as a major source of support for them and helped them cope with the rejection and stigma associated with their sexual orientations. They further claimed that the stigma and rejection contributed to poor mental health of most LGBTQ+ persons with most of them seeking asylum in more inclusive and welcoming jurisdictions. Conclusion Members of the LGBTQ+ community in Ghana face stigma and societal pressures in their families and public spaces, creating stress that contributes to mental health challenges. We recommend that the Government of Ghana through the Ministry of Gender, Children and Social Protection and the Ghana Health Service increases public education to improve cultural competence and inclusivity of this vulnerable population in society to reduce stigma and discrimination.